KAJIAN KESESUAIAN BUDIDAYA LAUT KARAMBA JARING APUNG PERAIRAN GUGUSAN PULAU LAUT KEPULAUAN KABUPATEN KOTABARU - Fatmawati Fatmawati; Baharuddin Baharuddin (EnviroScienteae, 2021)
The research has been carried out in the waters of the Pulau Laut Islands cluster, located in the southern part of the Pulau Laut Island, Kotabaru Regency, South Kalimantan Province, Indonesia. The conduct of the study was to determine the level of cages culture suitability for mariculture of marine fish and the direction of the development of grouper Mariculture, based on the hydrodynamics of oceanography and physical chemistry parameters of waters. The waters suitability was determined based on the hydrodynamic parameter assessment and overlays of the physical chemistry quality requirements of the waters. Analysis was carried out using Arc View software. The results obtained a total area of the marine island waters is ± 13,906.70 hectare, the area of the waters that are very suitable (S1) is 484.17 hectares, adequate waters (S2) obtained an area of 985.96 hectare, conditional waters area (S3) 985.96 hectare and not suitable waters (N) is 11827.09 hectares. Mariculture development directions by considering limiting factors parameters during the west season from waves, currents and winds, it is recommended that in grouper Mariculture 74.18 ha of waters. It consists of 23.17 hectare of waters in the Tepian Mataja Strait and 51.02 hectare in the Karajaan Strait.